The Influence of Information Consumption from Social Media on the Improvement of Student Academic Literacy - Tiara A. Banjarnahor; Nadhifa Syalaisha; Tina Arsita Srg; Joharis Joharis (International Journal of Educational Evaluation and Policy Analysis, 2025)
This research aims to examine the influence of information consumption from social media on the improvement of students' academic literacy. Academic literacy is an important skill for students in understanding, analyzing, and critically utilizing scientific information. However, the low level of academic literacy in Indonesia has become a serious concern, especially in the digital era where social media has become the main source of information. This research uses a quantitative method with data collection techniques in the form of surveys among students. The research results indicate that the consumption of information from social media has both positive and negative impacts on academic literacy. Social media facilitates access to academic information, but it also has the potential to lower the quality of literacy due to the dominance of unverified information. This research provides strategic recommendations to enhance students' academic literacy, such as the wise use of social media and strengthening fact-checking skills. These findings are expected to help higher education institutions design policies that support the development of students' academic literacy in the digital era.